Preclinical models of middle cerebral artery occlusion: new imaging approaches to a classic technique - Jennifer D. Sokolowski; Sauson Soldozy; Khadijeh A. Sharifi; Khadijeh A. Sharifi; Pedro Norat; Kathryn N. Kearns; Lei Liu; Ashley M. Williams; Kaan Yağmurlu; Panagiotis Mastorakos; G. Wilson Miller; M. Yashar S. Kalani; et al. (Frontiers in Neurology, 2023)
Stroke remains a major burden on patients, families, and healthcare professionals, despite major advances in prevention, acute treatment, and rehabilitation. Preclinical basic research can help to better define mechanisms contributing to stroke pathology, and identify therapeutic interventions that can decrease ischemic injury and improve outcomes. Animal models play an essential role in this process, and mouse models are particularly well-suited due to their genetic accessibility and relatively low cost. Here, we review the focal cerebral ischemia models with an emphasis on the middle cerebral artery occlusion technique, a “gold standard” in surgical ischemic stroke models. Also, we highlight several histologic, genetic, and in vivo imaging approaches, including mouse stroke MRI techniques, that have the potential to enhance the rigor of preclinical stroke evaluation. Together, these efforts will pave the way for clinical interventions that can mitigate the negative impact of this devastating disease.